Hidden elements in the Algerian storyteller Said Boutadjine’s collection «My shoes, my socks and you» - Abdelali, Hanane; Boulfous, Zahira (Journal of Human Sciences, 2022)
Cultural criticism is one of the most prominent contemporarycritical trends generated bypost- modernist discourse¸ as it moved from text criticism to category criticism leading to the consideration of the literary text in the light of the culture that produced it. Its beginning goes back to the ninth decade of the last century with the America critic Vincent.B.Leitch’s call to the necessity of postmodern culturel criticism through his book (CulturalCriticism Literary Theory post structuralism)(1992).It deals with the search for the cultural aspect inside the literary text by describing this latter as a cultural discourse. So¸ this approach looks for the cultural contexts embedded in the literary text then reveal them and uncover their significance.Since the contemporary short story in general - and the Algerianshort story in particular - includes within it a set of implicit cultural categories such as thepolitical¸ social and the religious ones¸ this recherch will attempts to introduce a cultural approach to the story collection « My shoes my socks and you » of the Algerian storyteller «Said boutadjine »accordingtotheculturalcriticismmechanics this is in order to monitor and extract the hidden categories the text encloses and highlight their effectiveness and function within the textual structure.